The Effect of Photodynamic Therapy with Photosan and Different Concentrations of Methylene Blue on Candida Albicanshad been Grown on Denture - Ali SalehiMazandarani; Shahram Amini; Amir Mansour Shirani; Mones Sanjaripour (Isfahan University of Medical Sciences, 2022)
In some studies, photodynamic therapy with some light sources and light-absorbing materials were used against Candida. In this study, the antifungal effects of 630 nm photosan with different concentrations of methylene blue on Candida albicansthat had been grown on dentures was investigated. In data searches no similar study was found.Materials & Methods:This experimental laboratory study was performed in Isfahan Azad University in 2019-2020. On total 26 similar dentures were prepared. Suspension of 0.5 McFarland Candidia albicanswas inoculated on the dentures. The samples were put into three groups (seven in each) with different concentrations of methylene blue (0.1, 0.01, 0.001 g/l) and photosan with a wavelength of 630 nm was used. Five control samples including untreated control, photosan alone and three controls with methylene blue concentrations only were considered. The number of colonies was counted using manual and ocular methods. Data were analyzed with T-test, ANOVA.Results:The mean number of Candida albicansgrown on dentures after photodynamic therapy and different concentrations of methylene blue was significantly different from control groups (p value < 0.05). The mean number of Candida albicansgrown on dentures after photodynamic therapy were significantly different between the three concentrations of methylene blue (p value < 0.001). Methylene blue with a concentration of 0.1 mg had significantly better efficacy against candida compared with two other concentrations (p value < 0.001).Conclusion:Photodynamic therapy with photosan and methylene blue with a concentration of 0.1 provided better results compared to others in reducing Candida albicans